Performance Management and Student Mathematic Disposition through a Posing Problem Approach - Inoviliana Inoviliana; Sakinah Ubudiyah Siregar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to determine the performance management and mathematical disposition of students through the problem posing approach. This research uses quasi experimental research. The population in this study were 149 students of SMK Sumber Mulyo. The research sample was the cluster random sampling technique (random group sample), that is, one class was selected as a sample subject to treatment through random selection, namely students of class XI SMK TSM totaling 30 students. The results showed that the level of influence between the problem posing approach variable on performance management and students' mathematical dispositions had a high effect. The results of testing the research hypothesis testing problem posing approach to performance management can be seen that the tcount value is 7.560 and ttabet is 1, 781 so that tcount ≥ ttable then Ha1 is accepted, that is, there is a positive and significant influence between the problem posing approach to performance management. Furthermore, the results of the research hypothesis test of the problem posing approach to mathematical disposition, it is known that the tcount value is 6.630 and the t table is 1.981 so that tcount ≥ ttable then Ha2 is accepted, namely that there is a positive and significant influence between the problem posing approach to mathematical disposition.